Detection of the PrP gene in Junin sheep - Rivera J., Kamilo (2015)
The aim of this study was to establish the frequency of resistance and susceptible genotypes to scrapie in the Junin sheep breed. For this, 56 blood samples were collected in a sheep farm in the central highlands of Peru. The DNA was extracted and the PCR products were analyzed by enzymatic digestion using restriction endonucleases that recognize the PrP gene polymorphisms. Four of the 5 haplotypes reported for the PrP gene were identified: ARR (48.2%), ARQ (35.7%), AHQ (10.7%) and VRQ (5.4%). In addition, 7 of the 15 reported genotypes for the Prion gene were found: ARR/ARR (17.9%), ARR/AHQ (10.7%), ARR/ARQ (42.9%), ARQ/AHQ (10.7%), ARQ/ARQ (7.1%), ARR/VRQ (7.1%) and ARQ/VRQ (3.6%). Finally, 82.1% of the animals had genotypes resistant to the disease and 17.9% showed genotypes of susceptibility.